Swipe now, regret later? How credit cards reduce the appeal of safe choices - Hung, Hui-Hsi; Cheng, Yin-Hui; Chuang, Shih-Chieh; Wang, Tzu-Ming (Frontiers in Psychology, 2025)
Most research on the influence of decision-making on the compromise effect has focused on paying with cash rather than with a credit card. The experimental investigations of this paper revealed that the compromise effect was reduced when consumers paid with a credit card rather than with cash, and that the pain of paying played a mediating role between the payment form and the occurrence of the compromise effect. In addition, the authors successfully excluded alternative explanations such as differences in price, product category, and attribute importance. Finally, this paper showed that the impact of cash payments on the compromise effect was stronger among tightwads than among spendthrifts.